2005
DOI: 10.1111/j.0956-7976.2005.00806.x
|View full text |Cite
|
Sign up to set email alerts
|

Orientation Congruency Effects for Familiar Objects

Abstract: How do observers recognize objects after spatial transformations? Recent neurocomputational models have proposed that object recognition is based on coordinate transformations that align memory and stimulus representations. If the recognition of a misoriented object is achieved by adjusting a coordinate system (or reference frame), then recognition should be facilitated when the object is preceded by a different object in the same orientation. In the two experiments reported here, two objects were presented in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 39 publications
0
6
1
Order By: Relevance
“…Consequently, there is a reduction in the mental rotation effect, similar to our results. Although in previous studies, the internal reference frame effect was restricted only to a brief interval between successive stimuli (e.g., less than 100 ms) (Graf, Kaping, & Bülthoff 2005; Robertson, Palmer, & Gomez 1987) and the repeated response in the normal–backward discrimination task (Robertson, Palmer, & Gomez 1987), our Experiments 1 and 2 could not rule out the possibility of an internal reference frame effect. In fact, in our Experiment 1, the interaction between AOA of the preceding stimulus and AOA of the current stimulus was significant (see Table 2), indicating that the mean RTs for the current trials were influenced by the relation between the orientations of the preceding stimulus and the current stimulus.…”
Section: Methodscontrasting
confidence: 55%
See 1 more Smart Citation
“…Consequently, there is a reduction in the mental rotation effect, similar to our results. Although in previous studies, the internal reference frame effect was restricted only to a brief interval between successive stimuli (e.g., less than 100 ms) (Graf, Kaping, & Bülthoff 2005; Robertson, Palmer, & Gomez 1987) and the repeated response in the normal–backward discrimination task (Robertson, Palmer, & Gomez 1987), our Experiments 1 and 2 could not rule out the possibility of an internal reference frame effect. In fact, in our Experiment 1, the interaction between AOA of the preceding stimulus and AOA of the current stimulus was significant (see Table 2), indicating that the mean RTs for the current trials were influenced by the relation between the orientations of the preceding stimulus and the current stimulus.…”
Section: Methodscontrasting
confidence: 55%
“…The second factor that was not considered in Experiments 1 and 2 was the internal reference frame effect (Graf, 2006; Graf, Kaping, & Bülthoff 2005; Jolicœur, 1990; Robertson, Palmer, & Gomez 1987). An internal reference frame can be regarded as a coordinate system for establishing position and orientation relative to the observer.…”
Section: Methodsmentioning
confidence: 99%
“…The extent of the involvement of each of these networks for object knowledge retrieval is determined by a combination of factors, including the object’s size (e.g., Grèzes et al, 2003), the specific demands of a concurrent task (e.g., Creem & Proffitt, 2001; Yee et al, 2013), and, as we show here, the object’s orientation with regards to action (c.f., Graf et al, 2005). …”
Section: Discussionmentioning
confidence: 99%
“…Although perceptual exposure to objects automatically evokes their potential for action as discussed earlier, the positioning of an object with respect to the observer can influence access to these action properties, likely due to the dependence of imaginary rotation mechanisms on the same left parietal networks that are engaged in motor planning (Creem et al, 2001). Additionally, graspable objects tend to be categorized according to a canonical-for-grasp viewpoint; as a result, objects in altered orientations are recognized slower and less accurately than objects in the canonical orientation; this recognition process appears to occur by similar mental rotation adjustments of the perceptual coordinate system to reorient the object to the canonical position for object use (Graf, Kaping, & Bülthoff, 2005; Kravitz, Vinson, & Baker, 2008; Petit, Pegna, Harris, & Michel, 2005). …”
Section: Effects Of Perceptual Properties On Object Knowledge Retrievalmentioning
confidence: 99%
“…Perhaps the most compelling example is neuropsychological patients who recognize objects regardless of orientation, but cannot interpret object orientation [10], [11]. Likewise, some experimental studies have found that object identity is determined before object orientation [12] while others have shown that orientation can be primed independently of shape [13]. Furthermore, viewpoint costs are not always observed and seem to depend on a variety of stimulus and task variables [14]–[16].…”
Section: Introductionmentioning
confidence: 99%